The battle of the Atlantic how the allies won the war - Dimbleby, Jonathan (Oxford University Press, 2016)
A gripping tale that transforms our understanding of the Second World War The Battle of the Atlantic was - though often overlooked - crucial to victory in the Second World War. If the German U-boats had prevailed, the maritime artery across the Atlantic would have been severed. Mass hunger would have consumed Britain, and the Allied armies would have been prevented from joining in the invasion of Europe. There would have been no D-Day. Through fascinating contemporary diaries and letters, from the leaders and from the sailors on all sides, Jonathan Dimbleby creates a thrilling narrative that uniquely places the campaign in the context of the entire Second World War. Challenging conventional wisdom on the use of intelligence and on Churchill's bombing campaign, The Battle of the Atlantic tells the epic story of the decisions that led to victory, and the horror and humanity of life on those perilous seas